The antibody catalysis route to the total synthesis of epothilones - Sinha, Subhash C. (The National Academy of Sciences, 1998)
An efficient monoclonal aldolase antibody that proceeds by an enamine mechanism was generated by reactive immunization. Here, this catalyst has been used in the total synthesis of epothilones A (1) and C (3). The starting materials for the synthesis of these molecules have been obtained by using antibody-catalyzed aldol and retro-aldol reactions. These precursors were then converted to epothilones A (1) and C (3) to complete the total synthesis.